Alert for an epidemic of oral cancer due to use of the betel quid substitutes gutkha and pan masala: a review of agents and causative mechanisms - Nair, Urmila; Bartsch, Helmut; Nair, Jagadeesan (Mutagenesis, 2004)
Abstract. In south‐east Asia, Taiwan and Papua New Guinea, smoking, alcohol consumption and chewing of betel quid with or without tobacco or areca nut with or w
Gesehen am 10.12.2020